The POPPY Study: Developing a Model of Family-Centred Care for Neonatal Units - Staniszewska, S; Brett, J; Redshaw, M; Hamilton, K; Newburn, M; Jones, N; Taylor, L (2012)
Background: The concept of family-centred care in neonatal practice has become increasingly recognised internationally. The underlying philosophy puts parents and the family at the centre of health care and promotes "individualised, flexible care." Aims: To develop the first international model of family-centred care based on strong parental collaboration in the synthesis of robust research evidence to generate the philosophy, principles, model, and indicators for implementation. Methods and Synthesis: Seven key steps were followed to develop the POPPY model of care collaboratively with parents. Step 1 drew on the POPPY systematic review to identify effective interventions. Step 2 drew on the POPPY qualitative study to identify good parent experiences. Step 3 identified the philosophy and principles of the POPPY model of care. Step 4 identified the key stages of the POPPY model of care. Step 5 populated the POPPY model of care with data from steps 1 and 2. Step 6 developed the indicators of family-centred care; and Step 7 undertook some initial testing with parents and practitioners. Results: Seven key stages of the parents' journey through their neonatal unit experience were identified and formed the architecture of the POPPY model of care. These include: before admission to the unit, admission, early days, growing and developing, transfers between units and between levels of care, preparing for discharge, and transition to home and at home. A philosophy, a set of principles to underpin the model, and a set of indicators to guide implementation in neonatal units were developed. Conclusion: The POPPY model of family-centred care provides the first robust, collaboratively developed, parent-centred model, which can be implemented to deliver high quality care to parents of preterm infants. Implications: Implementing the POPPY model could help neonatal units to develop parent-focused services which better meet parents' needs for information, communication and support, key elements of family-centred care. © 2012 Sigma Theta Tau International.